(untitled) (Dermatology Reports, 2016)
The etiology of androgenic alopecia (AGA) involves several factors, including genetics, androgens, age and nutrition. Digit-length ratio of the index and ring finger (2D:4D) is an indicator of prenatal exposure to sex hormones. There is a paucity of studies that systemically review the possible positive predictive value of 2D:4D in the development of AGA. We performed a single-site, descriptive-analytical study among a racially homogeneous population. Our results revealed that no significant association was determined between right 2D:4D and AGA severity within our entire population (P=0.384, r=0.025), however a positive correlation coefficient was identified in subjects above the age of 40. Based on the receiver operating characteristic curve analysis, 2D:4D does not predict the development of AGA. AGA is truly a multifactorial disease. Further, our findings suggest that increased in utero exposure to androgens as a fetus does not predispose men to develop AGA.